The interpretation of the folk-dancing melodies in the creation of native composers. - T.P. Reshetnikova; T.D. Furdak (Academy of Cognitive and Natural Sciences, 2006)
In article the modem tendencies and peculiarities of murpretatnm of folk dancing melodies in the creation of Ukrainian composers are considered. Various forms of using folklore sources in professional music of the past and die present are analyzed.